1953
DOI: 10.1128/jb.65.2.113-121.1953
|View full text |Cite
|
Sign up to set email alerts
|

Host Controlled Variation in Bacterial Viruses

Abstract: Passage through new hosts or new tissues is a widely used method for altering the properties of viruses. In some instances selection of spontaneous mutants has been demonstrated to be the mechanism causing the variation (Luria, 1945). Nonhereditary mechanisms sometimes have been postulated, but since no such case has been analyzed sufficiently, it is often assumed that selection of mutants is the only possible mechanism. A detailed analysis of two cases of variation in two different bacterial viruses is report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 435 publications
(104 citation statements)
references
References 9 publications
2
102
0
Order By: Relevance
“…Mu G(-) plates with a frequency of 10-7 on the core type R1 strain E. coli C in agreement with [7]. Since E. coli C does not restrict foreign DNA [17], the low plating efficiency suggested to us that only host-range mutants of Mu G(-) plated on E. coli C. This was substantiated by experiments with purified LPS of E. coli C. Mu G(-) phage was not inactivated by LPS, but infectivity of the mutant phage Mu G(-)hl01 was completely blocked. The R1 core type therefore is not identical, but similar to the structure that is recognized by Mu G(-).…”
Section: Core Type Specificity Of G( + ) and G( -) Phagesupporting
confidence: 55%
“…Mu G(-) plates with a frequency of 10-7 on the core type R1 strain E. coli C in agreement with [7]. Since E. coli C does not restrict foreign DNA [17], the low plating efficiency suggested to us that only host-range mutants of Mu G(-) plated on E. coli C. This was substantiated by experiments with purified LPS of E. coli C. Mu G(-) phage was not inactivated by LPS, but infectivity of the mutant phage Mu G(-)hl01 was completely blocked. The R1 core type therefore is not identical, but similar to the structure that is recognized by Mu G(-).…”
Section: Core Type Specificity Of G( + ) and G( -) Phagesupporting
confidence: 55%
“…The host bacteria appeared to modify the phage so that phages with the incorrect modification were restricted in their replication in certain strains. 31,32 It was only 20 years later that genetic and biochemical studies revealed that this is caused by certain sequence-specific host endonucleases, now universally in use as restriction enzymes. The existence and role of messenger RNA was proven with phage-infected cells.…”
Section: Phages As Important Tools For Molecular Biology and Biotechnmentioning
confidence: 99%
“…Despite the ubiquity of RM systems in prokaryotic genomes [17], basic ecological and evolutionary aspects of these otherwise simple genetic elements are poorly understood [20]. Although RM systems have been discovered more than six decades ago due to their ability to protect bacteria from phage [32] and this is often assumed to be their main function [33], only a few experimental studies focused on the ecological and evolutionary dynamics of interactions between RM systems and phage [34,35]. Similarly, eects of RM systems on their host bacteria, such as their cost in individual bacteria due to self-restriction, began to be addressed quantitatively only recently [24,36].…”
Section: Discussionmentioning
confidence: 99%